Miracil D: Inhibition of Deoxyribonucleic Acid Polymerase-Deficient Escherichia coli - Rosenkranz, Herbert S. (1973)
Miracil D preferentially inhibited the growth of a deoxyribonucleic acid (DNA) polymerase-deficient Escherichia coli strain. This is taken to indicate that miracil D is capable of altering the DNA of living cells and that it may thereby be a potential mutagen and carcinogen.